Deprofessionalization of teachers’ occupation: sociological analysis - Jūratė Litvinaitė (Acta Paedagogica Vilnensia)
Drawing on various sociological theories on the characteristics of work, profession, and service, the paper analyses the validity of the classification of teachers’ occupation as a profession, raising the question of what teaching is if not a profession. It also explores the trend of the changing social position of teachers’ professional activities in contemporary contexts. The introductory part of the article reveals the sociological content of the concepts of profession, work, and service. It explains what features allow these concepts to categorize various occupations. Based on Abbott’s (1988) analysis of the development of professions, it identifies the processes taking place in all professions causing them to lose their privileged status in society. The loss of status of professions is analysed through the concepts of professionalization, deprofessionalization, bureaucratization, and proletarianization. The characteristics of these processes are revealed based on various authors.Based on theoretical studies, the article analyses the results of empirical research conducted in the spring of 2023. The research ‘Teachers’ daily professional activities’ was designed using the photovoice method. The study involved 47 teachers with different professional experiences from different regions of Lithuania. The study revealed that teaching in contemporary contexts is experiencing all the symptoms of deprofessionalization and bureaucratisation, as well as intensive proletarianization of teaching: teachers are subjected to various forms of exploitation; alienation from the school and pupils is increasing, and teachers are being dehumanized. The article concludes with the discussion statements.